Analysis of Employee Workload at the Regional Food Service of Central Sulawesi Province - Ridhwan Ridhwan; Rukhayati Rukhayati; Abdul Rahman (International Journal of Health, Economics, and Social Sciences (IJHESS), 2020)
The formulation of the problem in this study is whether the workload of employees at the Central Sulawesi Province Food Service is by government regulation No. 46 of 2011, as for this study is to find out how to analyze the workload of employees at the regional food office of Central Sulawesi Province based on regulations government No. 46 of 2011. This research uses a qualitative descriptive method which is carried out through observation, interviews, and documentation—data collection. The results of this study indicate that the employees at the Central Sulawesi Provincial Food Service have optimally used 8 hours of work per day with the number of each field reaching 8-10 employees. According to the results of the comparison between the number of employees and the workload of each lot, they can carry out the task effectively because each assigned job is always done simultaneously. According to one employee, the provision of workload is very influential, especially on employee skills and behaviour.